The Impact of Nutrition and Early Dietary Introduction on the Prevalence, Severity and Management of Atopic Dermatitis in Infants. A Narrative Review - Makowska, Joanna; Darmoń, Jerzy; Windyga, Maria; Sieczka, Anna; Piegza, Natalia; Domańska, Karolina; Papuga, Aleksandra; Hejduk, Makary (Journal of Education, Health and Sport, 2026)
Background: Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin disease affecting up to 20% of children worldwide, characterized by epidermal barrier dysfunction and immune dysregulation. The increasing prevalence of AD has led to a discussion on efficacy of allergen avoidance versus early immune tolerance induction strategies. Aim: This review aims to synthesize current evidence on prenatal and early-life nutritional interventions and their impact on the prevalence and severity of AD in infants. Materials and Methods: A narrative review was conducted using a structured search of major electronic databases for studies published between January 2015 and March 2026. Eligible articles included original studies, systematic reviews, and meta-analyses addressing maternal diet, breastfeeding, complementary feeding, and micronutrient supplementation. Results: Current evidence does not support maternal elimination diets as a preventive strategy but suggests that greater dietary diversity may reduce risk of AD. Role of breastfeeding in preventing AD remains inconclusive. Early introduction of allergenic products between 4 and 6 months promotes oral tolerance, although its impact on AD incidence is inconsistent. Vitamin D deficiency correlates with increased disease severity, and its supplementation may be beneficial. Findings regarding omega-3 fatty acids remain heterogeneous. Hydrolyzed formulas and elimination diets are not recommended for routine prevention of AD. Conclusions: Nutritional strategies in AD are shifting toward proactive tolerance induction. Early dietary exposures play a key role in immune programming, although further research is needed to define optimal, individualized interventions.